LIKUIDITAS SAHAM, KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN - Mursalim Mursalim (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2011)
The objective of the paper is to investigate the effects of stock liquidity, dividend policy by the proxy of dividend payout ratio, and dividend policy by the proxy of dividend yield to the value of the firm. The research tested the hypotheses by using multiple regression. Hypotheses’ testing was conducted by using research sample of 25 banking company registered in the Indonesian Stock Exchange during the years of 2006-2008. The samples were determined by using purposive sampling method. The research result shows that stock liquidity has positive siginificant effect on the value of the firm. Other result shows that dividend policy by the proxy of dividend payout ratio has positive siginificant effect on the value of the firm. On the contrary, the result shows that dividend policy by the proxy of dividend yield does not have siginificant effect on the value of the firm. Keyword: stock liquidity, dividend policy, dividend payout ratio, dividend yield, value of the firm